PENGARUH LINGKUNGAN KERJA DAN LOYALITAS KERJA TERHADAP KINERJA KARYAWAN PADA PT. RODA PRIMA LANCAR KOTA TANGERANG - Erick Tri Widodo, Yohanes; Oktora, Jublina (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of work environment and work loyalty on employee performance at PT Roda Prima Lancar Tangerang City, both partially and simultaneously. The sampling technique used a saturated sample technique totaling 60 employees. Data collection techniques through primary and secondary data. The research method used is quantitative which is associative. The results showed that work environment and work loyalty had an effect on employee performance with a regression equation of Y = 2.272 + 0.239 X₁ + 0.647 X₂ with a coefficient of determination of 76.5%. The results of hypothesis testing partially affect the work environment on employee performance with the test results t count> t table or 3.756> 1.67155; then Ho₁ is rejected, and Ha₁ is accepted. Partially, work loyalty affects employee performance with the test results of t count> t table or 7.220> 1.67155; then Ho₂ is rejected, and Ha₂ is accepted. The results of hypothesis testing simultaneously the value of F count> F table or 93.031> 3.159; then Ho₃ is rejected, and Ha₃ is accepted. Thus it can be concluded that the results of the study indicate that the work environment and work loyalty affect employee performance at PT Roda Prima Lancar Tangerang City.